2022
DOI: 10.1029/2021gb007179
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Controls of Ecosystem‐Scale Methane Fluxes From a Subtropical Estuarine Mangrove: Multiscale, Nonlinearity, Asynchrony and Causality

Abstract: Mangroves are complex ecosystems subject to periodic and irregular changes in meteorology, tides, water quality and biological factors. Methane dynamics in mangroves and their dependence on biogeochemical controls across scales are poorly characterized using traditional parametric statistics. We measured the ecosystem‐scale methane flux (FCH4) using an eddy covariance system in a subtropical estuarine mangrove for two years. A combination of nonparametric statistical approaches, including singular spectrum ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 154 publications
0
2
0
Order By: Relevance
“…The high salinity in mangrove wetlands also inhibited ecosystem respiration by influencing the decomposition of soil organic matter, thereby modulating microbial‐mediated heterotrophic respiration (J. G. Liu & Lai, 2019). Furthermore, salinity is a crucial factor influencing CH 4 emissions from a biophysical perspective (J. Liu et al., 2020, 2022). The salinity has an impact on the sulfate levels in mangrove ecosystems, leading to an increase in redox potential and inhibition of CH 4 production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high salinity in mangrove wetlands also inhibited ecosystem respiration by influencing the decomposition of soil organic matter, thereby modulating microbial‐mediated heterotrophic respiration (J. G. Liu & Lai, 2019). Furthermore, salinity is a crucial factor influencing CH 4 emissions from a biophysical perspective (J. Liu et al., 2020, 2022). The salinity has an impact on the sulfate levels in mangrove ecosystems, leading to an increase in redox potential and inhibition of CH 4 production.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, salinity is a crucial factor influencing CH 4 emissions from a biophysical perspective (J. Liu et al, 2020Liu et al, , 2022. The salinity has an impact on the sulfate levels in mangrove ecosystems, leading to an increase in redox potential and inhibition of CH 4 production.…”
Section: Environmental Drivers Of Integrated Gwpsmentioning
confidence: 99%
“…Speci cally, we systematically reviewed the peer-reviewed publications between 2002 and 2023 reporting mangrove ux data using a Web of Science keyword search with the following terms: TOPIC: (mangrove AND Flux AND (GPP OR NEE)). This returned 24 related studies, of which three mangrove ux data are publicly available, located in the Everglades National Park in USA 71 , Yunxiao in mainland China 60,72 , and Mai Po in Hong Kong 73 (Supplementary Table 1). These sites provide half-hour GPP or NEE (Net Ecosystem Exchange), and the latter (NEE) was partitioned into GPP and ecosystem respiration following ref.…”
Section: Methodsmentioning
confidence: 99%
“…For example, there might be an underestimate in chamber‐based measurements of mangrove CH 4 emission without covering plant‐mediated pathways (e.g., stems and pneumatophores), which could be a considerable component of ecosystem CH 4 emission (Jeffrey et al., 2019; Zhang et al., 2022). On the other hand, the temporal varying patterns of mangrove CH 4 flux are far from clear, although few studies indicated the flux varied substantially at both short (hours to days) and long (months to years) time scales (Liu et al., 2022; Zhu, Sun, & Qin, 2021). In comparison with tidal marshes in which CH 4 flux is temperature‐dominated and varies seasonally (Al‐Haj & Fulweiler, 2020), the seasonal pattern of CH 4 flux in mangroves is less clear since the seasonality might be more regulated by salinity‐related factors (Zhu, Sun, & Qin, 2021).…”
Section: Introductionmentioning
confidence: 99%